Concepções da atividade física: Perspectivas para o fortalecimento da nação - Da Silva, Eliazar João [UNESP] (My University, 2007)
From the 1930's, particularly during World War II, some different phenomena rise as alternatives to strengthen the people's physical, especially in countries like Germany and Italy. Keeping different proportions, that phenomenon was seen in Brazil through a policy to increase the value of the physical activities, mainly during the Estado Novo. This article tries to analyze that policy.
Notions of physical activity: Perspectives for the strengthening of the nation
Keywords: Nation; Physical Education; Politics